PERAN MODEL EKONOMETRIKA DALAM MENENTUKAN INSENTIF PAJAK DAN DAMPAKNYA TERHADAP INVESTASI - Gadis Claudia; Devita Sari (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
Investment plays a key role in driving national economic growth. Therefore, the Indonesian government utilizes tax incentive policies as a means to increase the attractiveness of domestic investment. This study aims to analyze the role of econometric models in developing these policies and to assess their impact on investment growth. This study employed a literature review method, reviewing various sources, including journals, books, and previous research. The results demonstrate that econometric models help the government measure the effectiveness of tax incentives using data and figures. Tax incentives have been shown to encourage increased investment, although their impact is also determined by other factors such as economic stability, infrastructure availability, and ease of licensing. Therefore, integrated policies and ongoing evaluation are needed.